(untitled) (CIPEEX, 2025)
Introduction: The novel coronavirus disease (COVID-19) caused several health impairments, with the respiratory system being the most affected. Symptoms varied among individuals and included malaise, cough, dyspnea, and, in severe cases, acute respiratory distress syndrome (ARDS). Recent studies have also revealed that the virus can affect other systems, with the neurological system being particularly impacted, leading to clinical manifestations such as encephalitis, severe hypoxemia, encephalopathies, and, in some cases, Stroke. Objective: To describe the relationship between Stroke and COVID-19 infection, considering the age group of 16 to 49 years, based on data collected from hospitals in the municipality of Anápolis, aiming to contribute to scientific, academic, and professional health fields. Methodology: This was a cross-sectional, descriptive, and quantitative study. Data were obtained from 200 medical records between January 2020 and December 2021. Inclusion criteria were patients aged 16–49 who received care in the emergency department or were hospitalized at the Hospital Evangélico de Goiás, with confirmed Sars-Cov-2 infection. Exclusion criteria included patients without confirmed infection. Results: Among the analyzed patients, 63% exhibited only typical symptoms of the disease, 3.5% required transfer to the Intensive Care Unit (ICU), and 12% developed other significant complications, including 6% with pneumonia and 4% with nonspecific chest pain. No patient presented with Stroke. Conclusion: The majority of cases involved only typical symptoms of the disease, without severe complications. No cases of Stroke were identified.